A novel amalgamation of Gd2MoB2O9:CeF3 phosphor with ZnO: BaO: B2O3 glass using microwave synthesis for scintillation material applications. (June 2023) - Wongwan, W.; Yasaka, P.; Boonin, K.; Kim, H.J.; Kidkhunthod, P.; Horprathum, M.; Kaewkhao, J.
Abstract: This work investigates the physical, structural, optical, photoluminescence, and X-ray luminescence properties of Gd1.5 MoB2 O9 : 0.5CeF3 mixed 10ZnO:35BaO:55B2 O3 glass with a weight ratio of 1:9. The samples were prepared by heating with microwave synthesis technique varying the time from 5 min to 10 min. The structural studies were analysed using X-ray diffraction analysis (XRD) and the oxidation of cerium atom were analysed using X-ray analysis near edge spectra (XANES). An X-ray diffraction analysis to investigate the structure of samples using by a Shimadzu XRD–6100 diffractometer. XANES spectra of the Ce- L III edge for samples show peaks at ∼ 5728 eV, confirming the presence of Ce 3+ ion and Ce 4+ ion. A UV-VIS-NIR spectrophotometer was used to record the absorption spectra (Shimadzu, 3600) in the 200–1000 nm wavelength. The photoluminescence of the sample show overlapping between excitation and emission spectra in the range of 300–450 nm by monitoring at room temperature with a spectrofluorophotometer (Cary-Eclipse). These emissions correspond to the 5d – 4f transitions of Ce 3+ ion. From radiation studies, the luminescence spectra under x-ray as source show the emission peak at 411 nm that corresponds to the 5d - 2 F5/2 and 5d - 2 F7/2 transitions of Ce 3+ ion. The samples with the highest intensity were compared with bismuth germanate oxide (BGO) crystals, which are used as radiation detectors, and were found to be as effective as 35.47% of the BGO crystals. The results obtained in the present work demonstrate that the current samples could be a potential candidate for use in scintillator applications. Highlights: Synthesis of phosphor mixed ZnO: BaO: B2 O3 glass by microwave synthesis. The strong emission spectra at 411 nm were observed. The Decay time of the phosphors with the lowest emission intensity was 75.35 ns. The integral scintillation efficiency of phosphors was 35.47% of the BGO crystal.